ENERGY FUNCTIONAL OF ROTATIONALLY SYMMETRIC HARMONIC MAPS FROM A BALL INTO A SPHERE - Chriestie E.J.C. Montolalu (JURNAL ILMIAH SAINS, 2016)
ABSTRACT A study in Rotationally Symmetric Harmonic Maps has been conducted in the past few decades. One of its well-known study is its application from a ball into a sphere in three dimensional space. This has been shown to be accurate by showing its energy function. This paper will show how to find an energy function for this case. Keywords: Rotationally Symmetric Harmonic Maps, Energy Functional FUNGSI ENERGI DARI PEMETAAN ROTASI HARMONIK SIMETRIS DARI BOLA KE SPHERE ABSTRAK Studi tentang Pemetaan Rotasi Harmonik yang simetris telah dilakukan selama beberapa dekade terakhir ini. Salah satunya yang paling dikenal adalah aplikasinya dari bola ke sphere dalam ruang dimensi tiga. Hal ini telah dapat ditunjukkan dengan akurat dengan membuktikan fungi energinya. Tulisan ini akan menunjukkan cara menemukan fungsi energi untuk masalah ini. Kata-kata kunci: Pemetaan Rotasi Harmonik Simetris, Fungsi Energi